Fiscal Responsibility Framework in Croatia : Lessons from the Past, Rules for the Future - World Bank (Washington, DC, 2013)
The Croatian Parliament enacted the Fiscal Responsibility Law (FRL) in November 2010. The law is designed to ensure long-term fiscal sustainability, fiscal discipline, and transparency, which have so far not been successfully enforced in previous legislation. The purpose of this note is to (i) review efforts to enhance fiscal management and stability in Croatia; (ii) present relevant international experience; and (iii) make recommendations for improving the FRL. The key recommendations stemming from the review of the law are the following: a) the temporary fiscal rule that the authorities plan first is appropriate. It calls for expenditure-based consolidation with clear annual spending reduction targets because revenue generation cannot be counted on to balance the budget over the medium term. The rule should be in place until the general government balance is reached because it would help reduce the debt-to-GDP ratio; b) setting up a legally and effectively independent authority to transparently monitor compliance with all elements of the fiscal responsibility framework, especially the fiscal rule, the three-year budget plan, and fiscal forecasts, is highly recommended; c) if the fiscal rule is to be effective, it should be supported by meaningful and enforceable sanctions; and d) also, the FRL should bind not only the current government and parliament but also future ones. Thus, as some other countries have done, the authorities could have considered enacting the FRL as an organic law with a two-thirds majority.